Gravity Monitoring of Underground Flash Flood Events to Study Their Impact on Groundwater Recharge and the Distribution of Karst Voids. Issue 4 (18th April 2020) - Watlet, A.; Van Camp, M.; Francis, O.; Poulain, A.; Rochez, G.; Hallet, V.; Quinif, Y.; Kaufmann, O.
Abstract: Flash flood events are expected to become increasingly common with the global increases in weather extremes. They are a significant natural hazard that affects karst landscapes, which host large resources of drinking water worldwide. The role played by underground flood events in the karst aquifer recharge is complex due to the heterogeneity of the basement which remains poorly understood. We present the analysis of 20 incave flash flood events affecting the Rochefort karst system (Belgium) using continuous gravity measurements at one single station and water level sensors installed in caves. Underground flood events typically produce a peak in the gravity signal, due to an increase in the associated mass change. After the flood, the gravity values drop but remain slightly increased compared to before the flood event. Via forward gravity modeling, we demonstrate that this remaining anomaly can be reasonably explained by the infiltration of local rainfall within the karst system rather than by allogenic recharge of the aquifer. Flash floods are mainly restricted to connected voids. This allows us to utilize them as proxies to investigate the distribution of cavities in the karst system. Forward modeling of the gravitational attraction induced by the mapped caves being flooded yields a gravity signal much smaller than the observed one. We conclude that at least 50% more cavities than those previously mapped are required to match the measured anomalies. This presents opportunities for implementing similar approaches in other diverse porous media, using gravity monitoring of hydrological processes (e.g., infiltration fronts, hydrothermalism, or tide effects in coastal aquifers) as proxies to characterize underground properties. Key Points: Gravity signals and water level data of 20 underground flash flood events are used to estimate their impact on the karst aquifer recharge The analysis of gravity data prior and after underground flood events does not suggest any significant recharge in the saturated zone the aquifer Forward gravity modeling of flood events affecting mapped caves evidences unknown cavities in the system